Mapeamento da contaminação por derivados do petróleo em região da sub-bacia do Rio Cascavel/PR - Beal, Simone Tolomeotti (2015)
The environmental impacts of gas stations are an alarming problem of contamination of soil and groundwater. Remedial or mitigating measures can only be effective from a correct diagnosis of contamination. Gas stations have wastewater as a wide range of potentially contaminating compounds, with special attention to so-called BTEX (Benzene, Toluene, Ethyl-benzene and xylenes), for its high toxicity provoking chronic diseases accounting for carcinogenic manifestation. The sub-basin of the river Cascavel-PR is an urban area that has physiographic characteristics that converge all groundwater and surface water at the municipal lake city favoring BTEX contamination resulting from activities in which petroleum products are handled. Opposite the occurrence of leaks and seepage of petroleum compounds should be emphasized to characterize the fragility or susceptibility of the subsurface environment. Due to this fact it is proposed to make the diagnosis of chemical contamination of the area generating thematic maps the identification of contamination by petroleum contaminants. The representation of these thematic maps using computational geoprocessing tools, which allows you to display the diagnosis as zones delineated by hierarchical levels of contamination. As diagnostic indicators were used the parameters pH, electrical conductivity, hydraulic conductivity in situ and BTEX concentrations. The parameters of the first tests were conducted as recommended by conventional standards and the concentrations of BTEX determined by gas chromatography. Knowledge of the current condition of contamination and hydraulic subsoil conditions (read hydraulic conductivity) allows you to make future projections of contamination, ie the possibility to model the temporal advancement of the contamination plume; constituting an important methodological tool allowing public managers proactive interventions and bring to the attention of potential risks on the part of the community involved. Contamination encountered by petroleum products with higher concentrations of xylenes and ethylbenzene in water occurred with alarming amount to public health. The soil under study were detected contaminants in harmful health proportions.